Analysis of Bound-Soliton States in a Dual-Wavelength Mode-Locked Fiber Laser Based on Bi2Se 3 - Ke-Xuan Li; Yan-Rong Song; Jin-Rong Tian; He-Yang Guoyu; Run-Qin Xu (IEEE Photonics Journal)
Wavelength switchable and dual-wavelength soliton operations are demonstrated in an erbium-doped fiber laser with three pieces of TI Bi2Se3 polyvinyl alcohol (Bi2Se3-PVA) film. Wavelength switchable operation from 1532 to 1557 nm could be achieved just by adjusting the pump power. With the appropriate settings of PC and pump power, a novel dual-wavelength soliton operation was observed. The dual-wavelength pulses operate at different mode-locked states. One is the single pulse mode-locking operation at 1532 nm, and the other one is the bound-soliton states at 1557 nm. However, the dual-wavelength soliton operation cannot be stable for a long time. The numerical results demonstrate that the separations of bound pulses have small variation and that the phase difference of bound pulses appear jumping change of $π $ .